Повышение порядка двумерных нормальных марковских полей - Мазманишвили, Александр Сергеевич; Сидоренко, Анна Юрьевна (НТУ "ХПИ", 2013)
The problem of design of the normal fields of Markov is considered with the increase of order. The algorithms of generation of the fields are presented 1th and 2th orders. It is shown that the got results can be applied in the tasks of acceptance of stochastic design.
Keywords: плотность распределения; функция распределения; моделирование стохастическое; алгоритм; генерация полей